(3GdajV GdEdgis - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3EYde Cf GdCaYGd hGdEfaYGdGJ JJaGhJ HMSH JaGhJ GdCehQ GdYbdjI hGdfaSGfjI hGdLSeGfjI hPdc Cfg cdeG cGf GdTF s
(3BNQgG (B:s
(3Hd Ydi WQM JaGUjdgG hGdEHGfI ef cd Yde efgG HbhGfjfgG GdcdjI hGdeSGFd GdLRFjI hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3EjQGf s
Keywords: (3GdadSaI hGdefWbs